2017
DOI: 10.1016/j.virol.2017.09.015
|View full text |Cite
|
Sign up to set email alerts
|

The Epstein-Barr virus miR-BHRF1 microRNAs regulate viral gene expression in cis

Abstract: The Epstein-Barr virus (EBV) miR-BHRF1 microRNA (miRNA) cluster has been shown to facilitate B-cell transformation and promote the rapid growth of the resultant lymphoblastoid cell lines (LCLs). However, we find that expression of physiological levels of the miR-BHRF1 miRNAs in LCLs transformed with a miR-BHRF1 null mutant (Δ123) fails to increase their growth rate. We demonstrate that the pri-miR-BHRF1-2 and 1-3 stem-loops are present in the 3′UTR of transcripts encoding EBNA-LP and that excision of pre-miR-B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 64 publications
2
21
0
Order By: Relevance
“…In different host cells, the expression profile of these viral miRNAs could be different and may serve as biomarkers for EBV-associated diseases (34)(35)(36)(37). Consistent with previous studies, which showed that the expression of miRNA from the miR-BHRF1 cluster was relatively restricted to lytic and latency III phases of EBV-infected B lymphoma cells (36,(38)(39)(40)(41)(42), we also observed that the miR-BHRF1 cluster is highly expressed in EBV-immortalized LCL cells and responds to LA treatment. In contrast, miR-BART induces tumor metastasis by regulating PTEN-dependent pathways and acts as a biomarker in nasopharyngeal carcinoma (33,43), suggesting a tissue-specific pathogenic role of the miR-BHRF1 cluster that regulates the development of EBV-associated B lymphoma malignancies in response to LA.…”
supporting
confidence: 88%
“…In different host cells, the expression profile of these viral miRNAs could be different and may serve as biomarkers for EBV-associated diseases (34)(35)(36)(37). Consistent with previous studies, which showed that the expression of miRNA from the miR-BHRF1 cluster was relatively restricted to lytic and latency III phases of EBV-infected B lymphoma cells (36,(38)(39)(40)(41)(42), we also observed that the miR-BHRF1 cluster is highly expressed in EBV-immortalized LCL cells and responds to LA treatment. In contrast, miR-BART induces tumor metastasis by regulating PTEN-dependent pathways and acts as a biomarker in nasopharyngeal carcinoma (33,43), suggesting a tissue-specific pathogenic role of the miR-BHRF1 cluster that regulates the development of EBV-associated B lymphoma malignancies in response to LA.…”
supporting
confidence: 88%
“…Studies also found that EBV miRNAs can inhibit EBNA1 expression, which may be EBV miRNAs a means to assist the host to escape immune surveillance [47]. In addition, EBV miR-BART6-5p was found to inhibit EBNA2 expression [48], and EBV-miR-BHRF1s could inhibit EBNA2 co-activated antigen EBNA-LP expression [49], suggesting that EBNAs and EBNA-LP could be regulated by EBV miRNAs to avoid immune surveillance and maintain EBV latency.…”
Section: Antigen Expressionmentioning
confidence: 97%
“…In addition to the regulation of lytic replication via down-regulation of BZLF1 and BRLF1 by BART miRNAs 82 , they have also been described to limit EBNA2, LMP1 and LMP2 expression [103][104][105][106] . In addition, BHRF1 miRNAs optimize the timing of EBNA-LP and BHRF1 expression for optimal B cell transformation 107,108 and suppress sumoylation that is required for efficient lytic replication induction 109 . Finally, both BART and BHRF1 miRNAs attenuate B cell receptor signaling and thereby desensitize infected B cells to lytic EBV replication induction 110 .…”
Section: Non-translated Rnas and Tumorigenesismentioning
confidence: 99%